The role of syntax in the translation of compound-complex sentences between Arabic and English - Al Shyiab, Mohammad M.; Wan Sulong, Muhammad W.; Abdul Jabar, Azidan M.; Mohd Kasim, Mohd Z. (Human Resources Management Academic Research Society (HRMARS), 2023)
Due to the syntactic differences between Arabic and English, translating compound-complex phrases is a difficult procedure that has presented a significant difficulty for translators. This demands a good understanding of syntax. Having a firm understanding of syntax is essential when translating complex statements. This essay investigates how syntax affects how these two languages translate compound-complex phrases. The goal of this study is to discover and evaluate the syntactic elements that influence how these sentences are translated. The review of the literature will go over earlier research that looked at syntax in translation and give a summary of what is known about translating compound-complex sentences between Arabic and English. The study used a qualitative research methodology to examine the syntactic constructions of compound-complex phrases in Arabic and English, identify the difficulties encountered by translators, and make recommendations for methods to enhance the translation procedure. The results demonstrate that accurate translation of compoundcomplex sentences requires a solid command of syntax, and that translators must be aware of the distinctions between Arabic and English's syntactic structures as well as the text's context and purpose in order to do so. In order to improve the translation of compoundcomplex phrases between Arabic and English, the study offers suggestions and emphasizes the significance of syntax in translation.